Role Playing dalam Pembelajaran Pendidikan Pancasila Dan Kewarganegaraan - Nurgiansah, T Heru; Hendri, Hendri; Khoerudin, Cep Miftah (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2021)
AbstractThe majority of students consider the subjects of Pancasila and Citizenship Education to be boring subjects. The content of many materials, monotonous media and learning models, until the teacher's ability in classroom management is signalled to be the cause that results in less motivation, activeness, and student achievement. A proper learning model is needed to overcome these learning problems, namely role-playing learning models. The purpose of this study was to see the phenomenon of learning Pancasila and Citizenship Education in Class X SMA PGRI 1 Kasihan Bantul. The research method used is the qualitative method with descriptive studies. Data collection techniques in the form of observations, interviews, and documentation. The results showed that the use of Role-Playing learning models succeeded in making the learning atmosphere more interesting, active, and successful in improving students' academic abilities, especially in the material of the National Legal and Judicial System._________AbstractMayoritas siswa menganggap mata pelajaran Pendidikan Pancasila dan Kewarganegaraan adalah mata pelajaran yang membosankan. Isi materi yang banyak, media dan model pembelajaran yang monoton, sampai kemampuan guru dalam pengelolaan kelas disinyalir menjadi penyebabnya yang mengakibatkan motivasi, keaktifan, dan prestasi siswa menjadi kurang. Diperlukan sebuah model pembelajaran yang tepat untuk mengatasi permasalahan belajar tersebut, yakni model pembelajaran Role Playing. Tujuan penelitian ini adalah untuk melihat fenomena pembelajaran Pendidikan Pancasila dan Kewarganegaraan di Kelas X SMA PGRI 1 Kasihan Bantul. Metode penelitian yang digunakan adalah metode kualitatif dengan studi deskriptif. Teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukan bahwa penggunaan model pembelajaran Role Playing berhasil membuat suasana pembelajaran semakin menarik, aktif, dan berhasil meningkatkan kemampuan akademik siswa khususnya pada materi Sistem Hukum dan Peradilan Nasional.